2015
DOI: 10.1007/s10974-015-9405-5
|View full text |Cite
|
Sign up to set email alerts
|

Dyad content is reduced in cardiac myocytes of mice with impaired calmodulin regulation of RyR2

Abstract: In cardiac muscle, calmodulin (CaM) regulates the activity of several membrane proteins involved in Ca(2+) homeostasis (CaV1.2; RyR2, SERCA2, PMCA). Three engineered amino acid substitutions in the CaM binding site of the cardiac ryanodine receptor (RyR2) in mice (Ryr2 (ADA/ADA) ) strongly affect cardiac function, with impaired CaM inhibition of RyR2, reduced SR Ca(2+) sequestration, and early cardiac hypertrophy and death (Yamaguchi et al., J Clin Invest 117:1344-1353, 2007). We have examined the ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…By promoting actin polymerization through N-WASP activation, BIN1+13+17 anchors and maintains these t-tubule microfolds to myofilament Z-disc structural protein α-actinin. Using transmission electron microscopy imaging, Dr. Franzini-Armstrong’s laboratory also observed t-tubule membrane infolding to lumen at t-tubule cross sections from mouse hearts [105], similar to the t-tubule microfolds reported in our study. These microfolds help trap extracellular ions, which create a diffusion barrier inside the t-tubule network.…”
Section: Multilayer Regulation Of T-tubules By Bin1supporting
confidence: 84%
“…By promoting actin polymerization through N-WASP activation, BIN1+13+17 anchors and maintains these t-tubule microfolds to myofilament Z-disc structural protein α-actinin. Using transmission electron microscopy imaging, Dr. Franzini-Armstrong’s laboratory also observed t-tubule membrane infolding to lumen at t-tubule cross sections from mouse hearts [105], similar to the t-tubule microfolds reported in our study. These microfolds help trap extracellular ions, which create a diffusion barrier inside the t-tubule network.…”
Section: Multilayer Regulation Of T-tubules By Bin1supporting
confidence: 84%
“…If mitochondria undergo fission, the obvious question is whether this fission results in the appearance of small mitochondrial profiles deriving from fragmentation of the normal elongated mitochondria. Mitochondrial fragmentation, resulting in the accumulation of smaller organelles, is easily detected in conditions of energetic stress and unbalanced Ca 2+ homeostasis (Wu et al, 2010;Iqbal and Hood, 2014;Lavorato et al, 2015). However, despite evidence for possible mitochondrial fission events, we find very little obvious evidence for fragmented mitochondria after electrical stimulation and practically no evidence after treadmill exercise.…”
Section: Discussionmentioning
confidence: 54%
“…Long-range effects occur in myopathies affecting calcium homeostasis, such as central core disease and malignant hyperthermia in which mitochondrial morphology, distribution and fragmentation are strongly affected (Boncompagni et al, 2009b;Lavorato et al, 2016). Prolonged unbalanced Ca 2+ homeostasis in the myocardium activates the fission process, resulting in increased frequency of mitochondrial profiles due to fragmentation, while also inducing prolonged nanotunneling extensions in the usually structurally conservative cardiac mitochondria (Lavorato et al, 2015(Lavorato et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators in this field have identified relevant and important molecular pathways linking obesity to cardiac dysfunction. In particular, alterations in myocardial Ca 2+ handling via changes in the functional expression of SERCA2A and ryanodine (RyR2) receptors(52, 57, 64) have been of interest, including a recent comprehensive paper demonstrating concurrent effects of RyR2 abnormalities to induced myocellular and β-cell dysfunction (65), affecting subcellular structures in addition to producing abnormalities in intracellular Ca 2+ handling (66). This shared dependence of the myocardium and β-cell highlights the need for further studies in to the mechanisms underlying the dysfunctional regulation of Ca 2+ in obesity/MetS.…”
Section: Hemodynamic and Cardiac Effects Of Obesity And The Metabolicmentioning
confidence: 99%